2019
DOI: 10.17645/mac.v7i1.1718
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer’s Margins Project: Access to Knowledge and Its Mobilization by LGBQ/T Cancer Patients

Abstract: Sexual and/or gender minority populations (LGBQ/T) have particular cancer risks, lower involvement in cancer screening, and experience barriers in communication with healthcare providers. All of these factors increase the probability of health decisions linked with poor outcomes that include higher levels of cancer mortality. Persistent discrimination against, and stigmatization of, LGBQ/T people is reflected in sparse medical curriculum addressing LGBQ/T communities. Marginalization makes LGBQ/T persons parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…With the help of our patient-advisors, language used for the survey invitations was reviewed and found to be inclusive for individuals of all backgrounds, cultures and sexual orientations. 24 Interested potential participants will be invited to follow a secure link to access the online anonymous survey hosted by Research Electronic Data Capture (REDCap). 25 Once the survey has been completed, participants will be asked if they are willing to take part in an online semi-structured interview/focus group session (phase II: self-selection sampling).…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…With the help of our patient-advisors, language used for the survey invitations was reviewed and found to be inclusive for individuals of all backgrounds, cultures and sexual orientations. 24 Interested potential participants will be invited to follow a secure link to access the online anonymous survey hosted by Research Electronic Data Capture (REDCap). 25 Once the survey has been completed, participants will be asked if they are willing to take part in an online semi-structured interview/focus group session (phase II: self-selection sampling).…”
Section: Methods and Analysismentioning
confidence: 99%
“…Social media campaigns will be posted on Facebook, Instagram and Twitter on the Cancer Rehabilitation Clinic, the CIUSSS Bas-St-Laurent and the researchers accounts. With the help of our patient-advisors, language used for the survey invitations was reviewed and found to be inclusive for individuals of all backgrounds, cultures and sexual orientations 24. Interested potential participants will be invited to follow a secure link to access the online anonymous survey hosted by Research Electronic Data Capture (REDCap) 25.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Our review discovered the need for clinician training and education to provide competent care to transgender individuals. Studies documented clinicians misgendering patients, 26,33,38 forcing repeated disclosure of patients' gender, 33 assumptions that all patients are heterosexual or gender-normative, 24,25 and contributing to transgender patients' feelings of alienation and invisibility. 16,26,27,33 Clinicians should promote the values of diversity, equity, and inclusion in clinical practice, by creating an open and safe space for transgender patients.…”
Section: Implications For Research Policy and Practicementioning
confidence: 99%
“…The articles that did attend to the psychosocial needs and experiences of transgender individuals provided more indepth descriptions of the experiences of transgender individuals with gendered cancer and raised important considerations for their psychosocial well-being. 17,[23][24][25][26][27] These studies described the disconnect that transgender individuals felt when they were diagnosed with a gendered cancer that did not match their gender identity. 17,23,26 Patients in these studies reported discomfort with joining support groups as individuals who did not identify with their sex assigned at birth.…”
mentioning
confidence: 99%
“…Transgender, non-binary, and Two-Spirit individuals have historically been underserved in clinical research and the broader healthcare setting (Burgwal et al, 2019; Jackson et al, 2021). As a result, these populations report lower involvement in health screening programs, longer wait times for care, decreased satisfaction with the care they receive, and face poorer health outcomes overall (Bryson et al, 2019). Healthcare avoidance among non-binary individuals is often attributed to anticipated and observed discrimination (Kcomt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%